Study of Supreme Court Decision Number 2580 K/Pdt/2016 on Divorce from Mixed Marriage between Indonesian and French Citizen - Maya Dyah Palupi; Rina Arum Prastyanti (Indonesian Journal Publisher, 2024)
This research examines the legal aspects related to divorce in mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA). In the context of marriage, which is a fundamental event in human life, the issue of mixed marriage is becoming increasingly relevant as interactions between countries increase. This research focuses on analyzing the Supreme Court's decision in Decision Number 2580 K/Pdt/2016, which dealt with a divorce between an Indonesian citizen and a foreigner from France. Using normative legal methods, this research explores the legal norms governing divorce in mixed marriages and assesses the consistency of the applicable law in Indonesia. The findings show that there are legal complexities at hand, especially regarding jurisdiction and children's rights, where the Supreme Court's decision has the potential to influence the handling of similar cases in the future. This research is expected to provide insight into the challenges of the Indonesian judicial system in dealing with international divorces as well as the legal implications resulting from the decision.